1984
DOI: 10.1111/j.1399-3011.1984.tb03148.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding affinities to rat brain synaptosomes – synthesis of biotinylated analogues of Substance P

Abstract: The synthesis of four biotinylated analogues of Substance P is described. The affinities of these analogues and of their complexes with avidin for the 125I‐Bolton Hunter Substance P binding sites on rat brain synaptosomes were determined. While these biotinylated peptides complexed to avidin retain a good biological activity on the guinea‐pig ileum bioassay, we observe a net decrease in their binding affinities in the central nervous system. The present study confirms that in the central nervous system the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous structure-activity studies (24,25) on SP have shown that modification of the Lys 3 side-chain has no…”
Section: Resultsmentioning
confidence: 94%
“…Previous structure-activity studies (24,25) on SP have shown that modification of the Lys 3 side-chain has no…”
Section: Resultsmentioning
confidence: 94%